Alex Cross Must Die: Alex Cross #32 - Patterson, James, 1947- (New York : Little, Brown and Company, 2023)
Detective Cross and his partner John Sampson are hot on the trail of the Dead Hours Killer, who is targeting commercial pilots, in the latest addition to the long-running series following Deadly Cross.
Series numeration from Goodreads.
Includes an excerpt for Cross Down (pages 3-16 at end of work).
New Book Winter 2023.
Keywords: Sampson, John -- (Fictitious character) -- Fiction; Cross, Alex -- (Fictitious character) -- Fiction; Terrorism -- Prevention -- Fiction; Police -- Washington (D C ) -- Fiction; African American detectives -- Fiction; Murder -- Investigation -- Fiction; Serial murders -- Fiction; Serial murderers -- Fiction; Washington (D.C.) -- Fiction; Detective and mystery fiction; Novels; Fiction; Thriller fiction; Detective fiction; Mystery fiction